2021
DOI: 10.2196/26427
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Patients Living With Chronic Conditions Using Video as an Educational Tool: Scoping Review

Abstract: Background Video is used daily for various purposes, such as leisure, culture, and even learning. Currently, video is a tool that is available to a large part of the population and is simple to use. This audio-visual format has many advantages such as its low cost, speed of dissemination, and possible interaction between users. For these reasons, it is a tool with high dissemination and educational potential, which could be used in the field of health for learning about and management of chronic di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…Digital empowerment helps people to increase their level of ehealth literacy which is defined by Chong et al (2020) [ 6 ] as the person’s ability to search for and understand health information on the internet in order to make decisions about health [ 6 ]. Ehealth literacy can be considered a useful tool for health education, promoting healthy lifestyles, reducing complications, or improving the follow-up of patients with chronic diseases [ 7 , 8 ]. However, do nurses use strategies to measure the empowerment of their patients?…”
Section: Introductionmentioning
confidence: 99%
“…Digital empowerment helps people to increase their level of ehealth literacy which is defined by Chong et al (2020) [ 6 ] as the person’s ability to search for and understand health information on the internet in order to make decisions about health [ 6 ]. Ehealth literacy can be considered a useful tool for health education, promoting healthy lifestyles, reducing complications, or improving the follow-up of patients with chronic diseases [ 7 , 8 ]. However, do nurses use strategies to measure the empowerment of their patients?…”
Section: Introductionmentioning
confidence: 99%
“…Patient advocacy was explained as empowerment of patients through education on their conditions, enabling them to be partners in the management. A recently conducted scoping review has shown that patient education is an effective tool in empowering patients with chronic diseases for self-management [ 52 ]. Based on the findings of this study, the understanding of PHC by both the students and their clinical preceptors augurs well for a good foundation in PHC training in the four South African medical schools.…”
Section: Discussionmentioning
confidence: 99%
“…The most developed resources by the participants were infographics and videos, two very useful resources to educate in healthcare and help patients self-manage themselves better [ 37 , 38 , 39 ]. Infographics could be even better accepted by patients than videos [ 38 ] and are a powerful resource for sharing knowledge among healthcare professionals [ 40 ] and spreading research results [ 41 ].…”
Section: Discussionmentioning
confidence: 99%